Predictors of treatment switching in the Big Multiple Sclerosis Data Network - Spelman, Tim; Magyari, Melinda; Butzkueven, Helmut; Van Der Walt, Anneke; Vukusic, Sandra; Trojano, Maria; Iaffaldano, Pietro; Horáková, Dana; Drahota, Jirí; Pellegrini, Fabio; Hyde, Robert; Duquette, Pierre; et al. (Frontiers in Neurology, 2023)
Background: Treatment switching is a common challenge and opportunity in real world clinical practice. Increasing diversity in disease modifying treatments (DMTs) has generated interest in the identification of reliable predictors of treatment switching across different countries, DMTs and time periods. Objective: The objective of this retrospective, observational study was to identify independent predictors of treatment switching in a population of relapsing remitting MS (RRMS) patients in the Big Multiple Sclerosis Data Network of clinical registries including the Italian MS registry, OFSEP of France, the Danish MS registry, the Swedish MS registry and the MSBase Registry. Methods: Patients were included in the final pooled analysis set if they had initiated at least one DMT during the relapsing remitting MS (RRMS) stage. Patients not diagnosed as RRMS or RRMS patients not initiating a DMT therapy during the RRMS phase were excluded from the analysis. The primary study outcome was treatment switching. A multilevel shared frailty time-to-event model was used to identify independent predictors of treatment switching. The contributing registry was included in the pooled analysis as a random effect. Results: Every 1 point increase in Expanded Disabiltiy Status Scale (EDSS) score at treatment start was associated with 1.08 times the rate of subsequent switching adjusting for age, sex and calendar year (adjusted Hazard Ratio (aHR) 1.08: 95% CI 1.07-1.08) (Table 2). Females were associated with 1.11 times the rate of switching relative to males (95% CI 1.08-1.14) whilst older age was also associated with an increased rate of treatment switching. DMT’s started between 2007-2012 were associated with 2.48 times the rate of switching relative to DMTs began between 1996-2006 (aHR 2.48; 95% CI 2.48-2.56). DMTs started from 2013 onwards were more likely to switch relative to the earlier treatment epoch (aHR 8.09; 95% CI 7.79-8.41). Conclusions: Switching between DMTs is associated with female sex, age and disability at baseline and has increased in frequency considerably in recent years as more treatment options have become available. Consideration of a patient’s individual risk profile needs to be taken into account when selecting the most appropriate switch therapy from an expanding array of treatment choices.